Javier Heraud, El Río - Vasquez Rodriguez, Pedro Denis (2019)
The present teaching proficiency piece of work has been done to get the license to practice as a Spanish Language and Literature teacher. The learning session has been designed for the fifth year secondary students of Antonio Torres Araujo school and it was held on the 5th of December, 2019. It is entitled “Javier Heraud, el río” (Javier Heraud, the river) and it is made up of three parts which are related to each other around the most meaningful Heraud´s poem called “El río” (The river). The learning session design describes the specific learning skills that fifth year secondary students must develop as well as the activities that have been planned according to their age which will let us observe students’ performance in class. The pedagogical support involves the methodology, didactics and evaluation which are essential for the learning session to be developed so as the students can be adapted to the new knowledge. The theoretical support considers the concepts and theories regarding the new knowledge, that is to say, Javier Heraud’s poetry which belongs to the Spanish Language and Literature area.